2021
DOI: 10.3389/fpsyt.2021.761203
|View full text |Cite
|
Sign up to set email alerts
|

EEG Microstates and Its Relationship With Clinical Symptoms in Patients With Schizophrenia

Abstract: Schizophrenia is a complex and devastating disorder with unclear pathogenesis. Electroencephalogram (EEG) microstates have been suggested as a potential endophenotype for this disorder. However, no clear dynamic pattern of microstates has been found. This study aims to identify the dynamics of EEG microstates in schizophrenia and to test whether schizophrenia patients with altered clinical symptoms severity showed different microstates abnormalities compared with healthy controls. Resting-state EEG data in 46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The abnormality of EEG microstates in patients with schizophrenia has been observed and reported in multiple previous studies (18)(19)(20)(21)(22), most of which involved patients with chronic conditions (19,23,24) or a mixed sample with no restriction on the course of disease (25)(26)(27)(28). For schizophrenia, the early stage represents the transition from the premorbid to the morbid state (7); a clear diagnosis and early intervention during this period can help avoid the interference of long course and numerous attacks of the disease.…”
Section: Introductionmentioning
confidence: 88%
“…The abnormality of EEG microstates in patients with schizophrenia has been observed and reported in multiple previous studies (18)(19)(20)(21)(22), most of which involved patients with chronic conditions (19,23,24) or a mixed sample with no restriction on the course of disease (25)(26)(27)(28). For schizophrenia, the early stage represents the transition from the premorbid to the morbid state (7); a clear diagnosis and early intervention during this period can help avoid the interference of long course and numerous attacks of the disease.…”
Section: Introductionmentioning
confidence: 88%
“…These four classical maps of EEG microstates are: (A) States associated with auditory processing; (B) States associated with visual processing; (C) States associated with cognitive control networks; and (D) States associated with dorsal attention networks[ 11 ]. EEG microstate analysis has been widely used in studies related to psychiatric disorders, showing schizophrenia[ 12 - 14 ], bipolar disorders[ 15 , 16 ], anxiety disorders[ 17 ], panic disorders[ 18 ], and insomnia[ 19 ]. For example, increases in microstate C and decreases in microstate D have been consistently identified as characteristic changes in individuals with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Cruz et al found that patients with schizophrenia and their siblings showed an increased presence of microstate class C and a decreased presence of microstate class D (18). One of our previous studies found that patients with schizophrenia exhibited an increased duration and coverage of microstate class C and decreased coverage and incidence of microstate class B, as compared with healthy controls (19). There is a growing body of evidence supporting that schizophrenia with violence might be a biologically based subtype of schizophrenia with neurobiological (20, 21) and neuropsychological deficits (22), and a study has classified it into a different phenotype (23).…”
Section: Introductionmentioning
confidence: 99%